Peran Pendidikan Pesantren Dalam Meningkatkan Kecerdasan Emosional Santri (Studi Kasus Di Pondok Pesantren Nurul Hidayah Sotek) - Rahman, Aditya Aulia (Universitas Islam Nahdlatul Ulama Jepara, 2024)
In the era of competitive globalization, developing emotional intelligence is crucial for individuals to achieve success in personal and professional life. This research aims to identify the role of education at the Nurul Hidayah Islamic Boarding School in increasing the emotional intelligence of students. The research method used is a qualitative approach with a case study design, involving observation, interviews and documentation. Research findings show that educational programs at the Nurul Hidayah Islamic Boarding School, which include training in empathy, cooperation and self-control, have succeeded in increasing the emotional intelligence of students. Santri not only learn to manage emotions and build good interpersonal relationships, but also develop positive social skills. This research adds empirical evidence about the importance of Islamic boarding school education in developing emotional intelligence, filling the gap in literature that previously focused more on formal education in public schools. The theoretical implications of this research confirm that emotional intelligence can be improved through a holistic educational approach that includes intellectual, spiritual, moral and emotional aspects.Keywords: Emotional Intelligence, Islamic Boarding School Education, Nurul Hidayah Islamic Boarding School.